Facilitators and barriers to evidence adoption for central venous catheters post-insertion maintenance in oncology nurses: a multi-center mixed methods study - Funa Yang; Ka Yan Ho; Katherine Ka Wai Lam; Qi Liu; Ting Mao; Yan Wen; Liqing Li; Xiuxiu Yang; Na Xiao; Yanling Gao; Xiaoxia Xu; Frances-; et al. (BMC, 2024)
Abstract Background The post-insertion maintenance of central venous catheters(CVCs)is a common, vital procedure undertaken by nurses. Existing literature lacks a comprehensive review of evidence adoption for CVCs post-insertion maintenance specifically within the oncology context. This investigation assessed evidence-based practice by oncology nurses in the care of CVCs, elucidating facilitators and obstacles to this adoption process. Methods This was a sequential explanatory mixed methods study, executed from May 2022 to April 2023, adhering to the GRAMMS checklist. The study commenced with a cross-sectional study through clinical observation that scrutinized the adoption of scientific evidence for CVC maintenance, analyzing 1314 records from five hospitals in China. Subsequently, a semi-structured, in-depth interview with nurses based on the i-PARIHS framework was conducted to ascertain facilitators and barriers to evidence adoption for CVCs post-insertion maintenance. Fifteen nurses were recruited through purposive sampling. Descriptive statistics were used to summarize quantitative data, while content analysis was used to analyze qualitative data. Results An overall compliance rate of 90.0% was observed; however, two domains exhibited a lower adoption rate of less than 80%, namely disinfection of infusion connector and disinfection of skin and catheter. Three barriers and two facilitators were discerned from the interviews. Barriers encompassed (1) difficulty in accessing the evidence, (2) lack of involvement from nurse specialists, and (3) challenges from internal and external environments. Facilitators comprised (1) the positive attitudes of specialist nurses toward evidence application, and (2) the formation of a team specializing in intravenous therapy within hospitals. Conclusion There exists a significant opportunity to improve the adoption of evidence-based practices for CVC maintenance. Considering the identified barriers and facilitators, targeted interventions should be conceived and implemented at the organizational level to augment oncology evidence-based practice, especially the clinical evidence pertinent to infection control protocols. Trial registration This investigation was sanctioned by the Medical Ethics Committee of Henan Cancer Hospital (Number 2023-KY-0014).